PRESERVING PESANTREN EDUCATIONAL TRADITIONS: STRENGTHENING THE NAHDLIYYAH IDENTITY OF SANTRI IN THE ERA OF SOCIAL CHANGE - Syafaat, Imron Nur; Darwi, Mohammad s; Arifin, Syamsul (PROCEEDING OF INTERNATIONAL CONFERENCE ON EDUCATION, SOCIETY AND HUMANITY, 2024)
This study focuses on strategies to strengthen the Nahdliyah identity of santri in the era of social change through the implementation of the drill and practice method at Pesantren Al Maliki 2, Lumajang. A qualitative research methodology with a descriptive-analytical approach was employed to explore in depth how the repetition of Nahdliyah values through the reading of the buku syahadat (Nahdliyah practices book) and the implementation of daily activities can shape the character and leadership readiness of santri. Data were collected through interviews with kyai, ustadz, and santri; participatory observations; and analysis of relevant documents. The findings reveal that the drill and practice method consistently strengthen the internalization of Nahdliyah values, enhances solidarity among santri, and prepares them to become leaders in society. Routine activities such as reading the buku syahadat every Wednesday night and participating in Nahdliyah-based activities contribute to character development rooted in spirituality. The implications of this study affirm the importance of traditional pesantren educational methods in addressing modernization challenges while providing a practical framework for developing pesantren curricula based on local values.